1994
DOI: 10.1007/bf00134622
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ?-acetolactate synthase and ?-acetolactate decarboxylase in Lactococcus spp. and Leuconostoc spp.

Abstract: CeMiee extracts of tcucatrostof and &3culcpccut species were tested for their a-a&oWate syndmse and aacelolaetate dtmrboxylase activities. In ~~co~stuc meseffteroides subq. crmi3r&, Leacotwstoc mesentefoides subsp. ~senjeroldes and Leucon~~c factis, the Km of a-xetolactate synthase for pyruvate was close to 10 mM wm it was 30 mM in L~r~acc~ luctis subsp. lactis boom. ~~e~~actjs. The Km of a-acetolactate decarboxylase for a-xetoiactic acid was very low {ft.3 mM) in Letwaastoc specks in can-to Lactococcas luctis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
2
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 18 publications
2
26
2
1
Order By: Relevance
“…Similarly, separate addition of 1^10 mM branched chain amino acids (leucine, valine and isoleucine) also had no e¡ect on ALD activity. This result di¡ers from that obtained for L. lactis where a 14^40-fold increase in activity was observed in the presence of these amino acids [2].…”
Section: Enzyme Characterisationcontrasting
confidence: 55%
See 1 more Smart Citation
“…Similarly, separate addition of 1^10 mM branched chain amino acids (leucine, valine and isoleucine) also had no e¡ect on ALD activity. This result di¡ers from that obtained for L. lactis where a 14^40-fold increase in activity was observed in the presence of these amino acids [2].…”
Section: Enzyme Characterisationcontrasting
confidence: 55%
“…The current consensus is that diacetyl biosynthesis arises from spontaneous oxidative decarboxylation of ALA [2] and 13 C NMR has demonstrated that ALA is a direct precursor of both acetoin and diacetyl and that acetoin does not give rise to diacetyl [3]. Previous studies have suggested that diacetyl production may be enzyme-mediated by a putative diacetyl synthase catalysing the condensation of active acetaldehyde (hydroxyethyl-thiamine pyrophosphate (TPP)) with acetyl CoA [4], although such an enzyme has never been found in lactic acid bacteria despite exhaustive research [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…The pfl transcription start site is indicated with an arrow beside the sequence line. (21,22,35; also, see the introduction). Additionally, an L. lactis ldh strain lacking LDH would be expected to direct the pyruvate pools towards ␣-acetolactate via ALS and yield a higher amount of diacetyl (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…AL and the total amount of diacetyl plus acetoin were assayed as previously reported (39,59,61). Lactose, glucose, lactate, acetate, formate, ethanol, pyruvate, and butanediol production was determined by high-performance liquid chromatography with an HPX-78P anionexchange column (Bio-Rad Laboratories, Inc.) with 5 mM H 2 SO 4 as the eluent at 48°C.…”
Section: Methodsmentioning
confidence: 99%